Korea's Challenges Ahead-Lessons from Japan's Experience - Zoli, Edda (IMF Working Papers; Working Paper ;, 2017)
This paper draws out the parallels between Korea and Japan in terms of demographics, potential growth, balance sheets, asset prices and inflation. Korea's demographic trends seem to track Japan's with a lag of about 20 years. Low productivity in the service sector and labor market duality are common to both countries and need to be addressed with structural reforms. While Korea's corporate balance sheets are stronger than Japan's in the early 1990s, Korea needs to progress with the restructuring of nonviable firms to avoid the adverse consequences of delayed balance-sheet repair that Japan experienced. Given its strong fiscal balance sheet position, Korea can afford using fiscal policy actively to incentivize corporate restructuring and structural reforms and cushion their possible short-term adverse impact. Korea can prevent bubbles in asset prices that were at the origin of Japan's initial crisis with the continued use of macroprudential policies. Although Korea does not appear to be headed toward deflation, new econometric analysis presented in the paper suggests that aging will exert a downward drag on its inflation going forward.